THE EFFECTS OF PULMONARY HYPERTENSION ON OUTCOMES OF MITRAL VALVE SURGERY - ASHRAF, T; KHAN, T; ALI, HM; ZAFAR, H (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to assess the effect of pulmonary hypertension on the outcomes of mitral valve surgery in terms of operative mortality, dependence on inotropic agents, duration of ventilation, length of ICU, and hospital stay. This comparative study was conducted at the Department of Cardiac Surgery, Faisalabad Institute of Cardiology, from January 2018 to July 2018. A total of 138 cases (69 in each group) were included in the study. Patients with mild or moderate PHT were enrolled in group A, and patients with severe PHT were in group B. Required surgery was performed. Outcomes, including operative mortality, duration of mechanical ventilation postoperatively, dependence on inotropic agents in ICU, and length of stay in ICU as well as hospital, were noted in both groups during intensive care stay. Difference between the two groups in terms of mean duration of mechanical ventilation (10.58±2.79 vs. 10.96±3.42 hours; p-value=0.480), mean duration of inotropic support (8.55±2.75 vs. 9.45±3.92 hours, p-value=0.122), mean length of ICU stay (2.97±1.34 vs. 3.32±1.40 days, p-value=0.138) and mean length of hospital stay (12.3±3.8 vs. 12.6±4.1 days, p-value=0.684) was not statistically significant. In patients with severe pulmonary hypertension, mitral valve replacement was found equally safe compared to those with mild to moderate pulmonary hypertension.